A Note on an Outbreak of Cowpea Mild Mottle Virus (CPMMV) in Common Bean in the River Nile State, Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
An outbreak of a devastating virus disease occurred in common bean(Phaseolus vulgaris) in Berber area, the River Nile State, during the 2004/2005 croppingseason, with symptoms of stunting and yellowing. The disease incidence reached a levelof more than 85% in all visited fields. One hundred fifty symptomatic samples, collectedfrom different fields at Hudeiba, Berber and Shendi, were blotted on nitrocellulosemembranes and tested for the presence of different viruses, using the tissue blotimmunoassay (TBIA) technique. The results of the serological tests revealed that 95% ofthe samples were positive for cowpea mild mottle virus (CPMMV). Among the commonbean genotypes screened for resistance to CPMMV, only RO/2/1 and Giza 3 wereresistant to the disease.
Keywords: CPMMV; common bean; River Nile State; Sudan